2023
DOI: 10.1097/wnr.0000000000001910
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the synthetic cannabinoid WIN55212 with tramadol on nociceptive thresholds and core body temperature in a chemotherapy-induced peripheral neuropathy pain model

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a significant adverse effect of many anticancer drugs. Current strategies for the management of CIPN pain are still largely unmet. The aim of this study is to investigate the antinociceptive potential of combining tramadol with the synthetic cannabinoid WIN55212, and to evaluate their associated adverse effects, separately or in combination, in a CIPN rat model, and to investigate their ability to modulate the transient receptor potential vanilloid 1 (TRPV1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…CB2 is expressed mainly in the immune system [ 57 ], while the CBD receptors are within CNS and throughout the body (i.e., TRPV1 is found on neurons in epithelial cells [ 58 , 59 ]). These receptors are part of the G-coupled protein receptors and are pharmacologic targets of interest as they control inflammation as well as other sensations (i.e., pain) [ 37 , 60 , 61 , 62 , 63 ]. Thus, it is not surprising that HU308 has been shown to decrease peripheral and ocular inflammation [ 55 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CB2 is expressed mainly in the immune system [ 57 ], while the CBD receptors are within CNS and throughout the body (i.e., TRPV1 is found on neurons in epithelial cells [ 58 , 59 ]). These receptors are part of the G-coupled protein receptors and are pharmacologic targets of interest as they control inflammation as well as other sensations (i.e., pain) [ 37 , 60 , 61 , 62 , 63 ]. Thus, it is not surprising that HU308 has been shown to decrease peripheral and ocular inflammation [ 55 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that to reduce the pain associated with chronic inflammation, both CB2 and TRPV1 are beneficial. Thus, targeting both receptors should be considered in future studies [ 60 , 80 ]. Furthermore, longevity studies should be done to determine effects of long-term drug use with CBD or HU308 in combination with cART, especially in regards to latency.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is an overlap between the opioid and cannabinoid systems in pain modulation. Both systems, connected through GPCRs, share similar intracellular signaling pathways, suggesting a synergistic effect between cannabinoids and opioids for pain relief [49].…”
Section: Key Modulators Of Pain Perception: Gpcr Ligandsmentioning
confidence: 99%
“…New drugs and therapies are required because a safe and effective treatment for chronic pain has not yet been developed. Pharmaceutical research focuses on effective analgesic drugs, with G-protein-coupled receptors (GPCRs) being a key focus in pain-relieving medication development [8][9][10]. Among them, adenosine metabotropic receptors (AR) modulators are increasingly being implicated in the antinociceptive and/or antihyperalgesic effects seen in various chronic pain models [2,[11][12][13].…”
Section: Introduction 1painmentioning
confidence: 99%